ASSESSMENT OF DETERMINANTS OF COMPLEMENTARY FEEDING PRACTICES IN MOTHERS OF LESS THAN 2 YEARS CHILDREN IN RURAL SETTING OF ISLAMABAD - Asif, Raima; Khan, Rukhsana; Babar, Nabeela Fazal (Journal of Ayub Medical College Abbottabad, 2020)
Background: Complementary feeding plays a significant role in determining child health up to 2 years of age. This study aimed to determine awareness among mothers about the timely initiation, nutritional adequacy and risks associated with early initiation of CF. Methods: A cross sectional study was conducted on 110 mothers living in Farash town Islamabad.List of women having index child less than 2 years was taken from LHW of that area.Subjects were chosen by simple random sampling.Mothers of children less than 2 years were included and children with any congenital abnormalities and mothers who didn’t give consent were excluded. Structured questionnaire was used for data collection.Descriptive statistic was used to categorize the study population. Summary statistics was used for continuous variable. Results: Ninety-six (87.3%) mothers had knowledge about CF and 88.2% practiced it. Thirty-three (30%) of the respondents had knowledge about correct age of CF and 35 (32%) mothers got CF information from the family members.The risks were known by only 46 (41.8%). Forty (36.4%) had introduced CF at 6 months.Sixty-one (55.5%) faced difficulties while introducing CF. Twenty-eight (45.90%) of children only accepted certain solid foods. Twenty-one (35%) children experienced vomiting. Association was seen between age appropriate CF practice with mother’s education (p=0.034), type of family (p=0.002), father’s profession (p=0.019) and total number of children (p=0.020). Conclusion: Improper feeding practices and inadequate knowledge regarding initiation of CF among mothers was observed.One third mothers initiated CF to their child at the age of 6 months.Same numbers of mothers were giving their child homemade food.Slightly less than half of the mothers knew about risks associated with early introduction of CF. Keywords: Mothers; Complementary feeding practices; Determinants